Association between peripheral eosinophilia, JESREC score, and olfactory dysfunction in patients with chronic rhinosinusitis - Zhang, Ling; Li, Haifeng; Wang, Tao; Wang, Zhu; Wu, Yang; Guo, Siquan; Li, Wenjing; Zhou, Yeru; Xue, Haixiang; You, Jianqiang (Frontiers in Immunology, 2024)
The purpose was to evaluate the relationship between peripheral eosinophilia, JESREC score and olfactory dysfunction in chronic rhinosinusitis (CRS) patients and to explore the accuracy and specific cut-points of the JESREC score in predicting olfactory dysfunction.In this cross-sectional, retrospective study, olfactory function was assessed by the Sniffin' Sticks 12-item test and multivariate logistic regression analyses were applied. Receiver operating characteristics curves were performed to derive accuracy and cutoff values for the JESREC scores of olfactory dysfunction criterion.Results: A total of 354 patients (mean [SD] age, 50.0 [14.9] years; 41.8% women) were included in the finally analysis. The prevalence of olfactory dysfunction was 46.3%. Individuals who had olfactory dysfunction were more likely to be male (64.6% vs. 52.6%), ECRS (39.0% vs. 7.9%), longer course (2.3 vs. 1.5 years), higher JESREC scores (8.5 vs. 4.5) and had higher proportion of nasal polyps (78.7% vs. 18.9%) and peripheral eosinophilia (3.3% vs. 1.4%). In logistic analysis,